The Good, the Bad, and the Ugly: Mycotoxin Production During Postharvest Decay and Their Influence on Tritrophic Host–Pathogen–Microbe Interactions - Bartholomew, Holly P.; Bradshaw, Michael; Jurick, Wayne M.; Fonseca, Jorge M. (Frontiers in Microbiology, 2021)
Mycotoxins are a prevalent problem for stored fruits, grains, and vegetables. Alternariol, aflatoxin, and patulin, produced by Alternaria sp., Aspergillus sp., and Penicillium spp., are the major mycotoxins that negatively affect human and animal health and reduce fruit and produce quality. Control strategies for these toxins are varied, but one method that is increasing in interest is through host microbiome manipulation, mirroring a biocontrol approach. While the majority of mycotoxins and other secondary metabolites (SM) produced by fungi impact host-fungal interactions, there is also an interplay between the various organisms within the host microbiome. In addition to SMs, these interactions involve compounds such as signaling molecules, plant defense and growth hormones, and metabolites produced by both the plants and microbial community. Therefore, studies to understand the impact of the various toxins impacting the beneficial and harmful microorganisms that reside within the microbiome is warranted, and could lead to identification of safe analogues for antimicrobial activity to reduce fruit decay. Additionally, exploring the composition of the microbial carposphere of host plants is likely to shed light on developing a microbial consortium to maintain quality during storage and abate mycotoxin contamination.